The Role of Youth in The Digitalization of Arts and Culture: A Case Study of Gondolio Arts in Banyumas Regency - Febi Faisal, Muhammad Agi; Hasanin, Hibatillah; Marlina, Marlina; Athayasani, Alya Naura; Ranjani, Ranjani (Public Administration, Faculty of Politics and Social Science, Universitas Jenderal Soedirman, Indonesia, 2025)
Preserving traditional culture is a major challenge in the era of globalization and digitalization. One of the cultural heritages whose sustainability is threatened is Gondolio art, a traditional musical art from Tambaknegara Village, Banyumas Regency. This art has significant historical value and social function, but faces various obstacles such as minimal youth regeneration, lack of infrastructure support, and the dominance of modern culture. This study aims to analyze the role of youth in the digitalization of Gondolio art as an effort to preserve traditional culture. The results of the study show that although the level of youth awareness of the importance of cultural preservation is quite high, their active participation in preserving Gondolio is still low. The use of digital technology, especially social media such as TikTok, Instagram, and YouTube, has been identified as an effective strategy to document, promote, and increase appreciation for Gondolio art. However, these digitalization efforts are still sporadic and require support from various stakeholders, including the government, arts communities, and youth. Key recommendations include cultural education for youth, optimizing the use of social media for promotion, and cross-sector collaboration to create sustainable digital-based preservation programs. With this approach, it is hoped that Gondolio art can remain alive and become an integral part of Indonesia's cultural identity in the modern era..